Low carbon investing - Elias, Jaan, (SAGE knowledge. Cases., 2016)
In August of 2014, the movement to divest fossil fuel investments from endowment portfolios was sweeping campuses across the United States, including Gifford Pinchot State University (GPSU). How should GPSU and its investment partner Commonfund react?